A Novel Highly Durable Carbon/Silver/Silver Chloride Composite Electrode for High-Definition Transcranial Direct Current Stimulation - Lingjun Li; Guangli Li; Yuliang Cao; Yvonne Yanwen Duan (Nanomaterials, 2021)
High-definition transcranial direct current stimulation (HD-tDCS) is a promising non-invasive neuromodulation technique, which has been widely used in the clinical intervention and treatment of neurological or psychiatric disorders. Sintered Ag/AgCl electrode has become a preferred candidate for HD-tDCS, but its service life is very short, especially for long-term anodal stimulation. To address this issue, a novel highly durable conductive carbon/silver/silver chloride composite (C/Ag/AgCl) electrode was fabricated by a facile cold rolling method. The important parameters were systematically optimized, including the conductive enhancer, the particle size of Ag powder, the C:Ag:PTFE ratio, the saline concentration, and the active substance loading. The CNT/Ag/AgCl-721 electrode demonstrated excellent specific capacity and cycling performance. Both constant current anodal polarization and simulated tDCS measurement demonstrated that the service life of the CNT/Ag/AgCl-721 electrodes was 15-16 times of that of sintered Ag/AgCl electrodes. The much longer service life can be attributed to the formation of the three-dimensional interpenetrating conductive network with CNT doping, which can maintain a good conductivity and cycling performance even if excessive non-conductive AgCl is accumulated on the surface during long-term anodal stimulation. Considering their low cost, long service life, and good skin tolerance, the proposed CNT/Ag/AgCl electrodes have shown promising application prospects in HD-tDCS, especially for daily life scenarios.